PENGARUH MEDIA SOSIAL TERHADAP PERNIKAHAN DINI DI MASA COVID-19 DI KOTA PADANGSIDIMPUAN PROVINSI SUMATERA UTARA - Jenny Yelina Rambe; Ris Artalina Tampubolon (Jurnal Education and Development, 2023)
Early marriage is a marriage that is carried out by someone, be it a man or a woman when his age has not yet reached true maturity . In accordance with Law no. 1 of 1974 concerning Marriage, it is stated that the age limit for marriage is 19 years for men and 16 for women and then revised again by Law no. 16 of 2019 the limit is 19 years for both men and women. This study aims to determine the effect of social media in encouraging teenagers to have early marriage in Padangsidimpuan City. The factors that will be studied in this study are the use of social media by teenagers such as Youtube, WhatsApp, Instagram, Facebook, Twitter. The analysis technique used is multiple linear regression analysis using SPSS software to simplify calculations. This type of research is quantitative research using a questionnaire, it can be concluded that the influence of social media on early marriage is 61.4%.